Symmetric and skew-symmetric {0, ±1} - matrices with large determinants - Greaves, Gary (2020)
We show that the existence of {±}-matrices having largest possible determinant is equivalent to the existence of certain tournament matrices. In particular, we prove a recent conjecture of Armario. We also show that large submatrices of conference matrices are determined by their spectrum.